Incidence, Treatment, and Survival of Patients With T-Cell Lymphoma, T-Cell Large Granular Leukemia, and Concomitant Plasma Cell Dyscrasias - Braunstein, Zachary; McLaughlin, Eric; Ruiz, Miguel; Wei, Lai; Bumma, Naresh; Benson, Don; Devarakonda, Srinivas; Chaudhry, Maria; Khan, Abdullah; Cottini, Francesca; Hanel, Walter; Baiocchi, Robert; et al. (Frontiers in Oncology, 2022)
T-cell malignancies are a group of heterogeneous disorders composed of primary cutaneous T-cell lymphomas (CTCL), peripheral T-cell lymphomas (PTCL), and T-cell leukemias, including T-cell large granular lymphocytic leukemia (T-LGLL). Cases of patients with combined T-cell malignancies and plasma cell dyscrasias (PCD) are reported in the literature, but these are mostly limited to case reports or small case series with less than 10 patients. Here, we describe the clinical course of 26 consecutive patients and report baseline characteristics and clinical outcomes including overall survival (OS), progression free survival (PFS), and objective response rates (ORR) in this unique population. There was no survival difference in patients with CTCL or T-LGLL and concomitant PCD when treated with standard therapy directed at the T-cell malignancy when compared to historical controls. However, patients with PTCL and concomitant PCD had significantly inferior outcomes with rapid progression and worse OS and PFS at 1.7 years (p=0.006) and 4.8 months (p=0.08) respectively when compared to historical controls for patients with PTCL, although the limited number of patients included in this analysis precludes drawing definitive conclusions. Treatment directed at the T-cell malignancy resulted in the eradication of the PCD clone in multiple patients including one with multiple myeloma (MM) who experienced a complete response after starting therapy directed at the T-cell malignancy. For patients with T-cell malignancies and concomitant PCD, treatment with standard T-cell directed therapies is recommended based on this analysis with continued follow-up and monitoring of the concomitant PCD. Further studies are needed to definitively elucidate the increased risk of relapse in patients with PTCL and concomitant PCD, and larger, multi-center cohorts are needed to validate these findings across T-cell malignancies and PCDs.